Hierarki Pengetahuan Gaib dalam Pemikiran Ibn Khaldun: Analisis Epistemologis atas Wahyu, Kasyf, dan Perdukunan - Afidah Wahyuni; Abdul Hakim Wahid; Rahmat Hidayatullah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This article examines the hierarchy of unseen knowledge in Ibn Khaldun’s thought by focusing on prophetic revelation, Sufi kashf, and divination. It employs library research and conceptual analysis, using the Muqaddimah as its primary source and scholarly works on Ibn Khaldun’s epistemology as secondary materials. The study demonstrates that Ibn Khaldun does not assign an equal epistemological status to all forms of knowledge concerning the unseen. Their differences are determined by the quality of the soul, source of knowledge, mode of reception, validity, and moral orientation of the recipient. Revelation occupies the highest level because it derives from the natural preparedness of the prophetic soul and divine assistance. Kashf is attained through spiritual discipline and is considered valid only when grounded in moral and religious rectitude. Divination occupies the lowest level because it relies on psychic ability, imagination, celestial objects, or demonic forces. These categories therefore constitute both an epistemological and a moral hierarchy.